Leveraging Social Media Marketing for Real Estate Sales: The Role of TikTok and Instagram in Building Customer Engagement and Trust - Kevin Arry Kasman; Veranus Sidharta (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines how social media marketing is leveraged to support real estate sales through TikTok and Instagram, focusing on the case of Dea Shanta Realtor. Real estate is a high-involvement product that requires trust, transparency, and repeated interaction before consumers move toward purchase decisions. Using a qualitative descriptive case study, data were collected through in-depth interviews, digital observation, and documentation of TikTok and Instagram content, audience responses, and sales-related interactions. The findings show that TikTok serves as a top-funnel channel for expanding reach, attracting new audiences, and driving traffic through short-form storytelling and algorithmic visibility. Instagram complements this role by serving as a visual catalog, a credibility-building space, and a platform for relationship maintenance through feeds, reels, stories, testimonials, and property updates. Customer engagement appears through comments, shares, saves, direct messages, WhatsApp inquiries, and requests for property details or site visits. Trust is built through transparent information, personal branding, fast responses, testimonials, and consistent communication. The study concludes that TikTok and Instagram contribute to real estate sales not directly as closing channels, but as strategic platforms for awareness, engagement, trust, and lead generation for property businesses seeking stronger, sustainable market competitiveness online.